El narcotráfico de metanfetamina en el sudeste asiático - MOYA BARBA, Guillermo (Journal of the Spanish Institute for Strategic Studies, 2023)
There has been a shift in the illicit drug market in South-East Asia, with non-synthetic drugs such as opium or heroin taking second place to synthetic drugs such as methamphetamine or ecstasy. This paper will analyse the current state of methamphetamine trafficking as the main synthetic drug in the South-East Asian drug trade, looking at regional and sub-regional trends, specifically in the so-called "Golden Triangle" of Myanmar, Laos and Thailand (and to a lesser extent China). Current factors such as the Covid-19 pandemic or the lack of governance in the Mekong countries will be highlighted as catalysts for drug trafficking, as well as the dangers to global and regional security posed by an expansion of methamphetamine trafficking by determining its current and proximate extent. Finally, it will examine the current state of international drug trafficking legislation and what it means for the prosecutability of those involved in drug trafficking networks through regional cooperation.